Morning cardio workouts - Kahn, June E., 1953- 4 0 16; 1964- Biscontini, Lawrence J. M.; 5 (Champaign, IL : Human Kinetics, 2007)
Details cardiovascular-oriented fitness routines that can be added to all types of morning schedules, describes how to customize a workout routine with options for indoor and outdoor activities, and provides information on activities for recovery, avoiding injuries, and cross-training.
Includes bibliographical references (p. 203) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Exercise.;Cardiovascular fitness.;Exercise.;Cardiovascular fitness; 20; 2